Liquid Waste Content Based on Chemical Parameters at Animal Slaughterhouse’s Inlet and Outlet: Study at Slaughterhouse X Jember District - Evi Dwi Atika Sari; Anita Dewi Moelyaningrum; Prehatin Trirahayu Ningrum (Journal of Health Science and Prevention, 2018)
Animal Sluaghterhouse (RPH) liquid waste contains organic matter, suspended solids, and colloid materials such as fat, protein, and cellulose with high concentrations that fall into the category of complex wastewater. RPH X is a RPH that uses Water Waste Treatment Plant (WWTP) in treating wastewater, although it has been equipped with WWTP there are still some problems in RPH X. The purpose of this research is to describe wastewater treatment and content of BOD, COD, TSS, NH3-N, pH and fatty oil at waste water in inlet and outlet of IPAL RPH X, Jember District. This research is a descriptive research. Technique of data collecting done by observation, interview, and laboratory test. The average of wastewater content test result in RPH X Jember Regency at inlet and outlet of IPAL is at safe limit of quality standard according to East Java Governor Regulation Number 72 Year 2013 except COD parameter at inlet that is equal to 277,6 mg / L. The average percentage of content in liquid waste in RPH X decreases from inlet to WWTP outlet except the pH parameter.